A microRNA panel compared to environmental and polygenic scores for colorectal cancer risk prediction - Raut, Janhavi R.; Schöttker, Ben; Holleczek, Bernd; Guo, Feng; Bhardwaj, Megha; Miah, Kaya; Schrotz-King, Petra; Brenner, Hermann (Nature Communications, 2021)
Circulating microRNAs (miRNAs) could improve colorectal cancer (CRC) risk prediction. Here, we derive a blood-based miRNA panel and evaluate its ability to predict CRC occurrence in a population-based cohort of adults aged 50-75 years. Forty-one miRNAs are preselected from independent studies and measured by quantitative-real-time-polymerase-chain-reaction in serum collected at baseline of 198 participants who develop CRC during 14 years of follow-up and 178 randomly selected controls. A 7-miRNA score is derived by logistic regression. Its predictive ability, quantified by the optimism-corrected area-under-the-receiver-operating-characteristic-curve (AUC) using .632+ bootstrap is 0.794. Predictive ability is compared to that of an environmental risk score (ERS) based on known risk factors and a polygenic risk score (PRS) based on 140 previously identified single-nucleotide-polymorphisms. In participants with all scores available, optimism-corrected-AUC is 0.802 for the 7-miRNA score, while AUC (95% CI) is 0.557 (0.498-0.616) for the ERS and 0.622 (0.564-0.681) for the PRS.
Gesehen am 17.08.2021